INHIBITION OF LIPID ACCUMULATION AND UPREGULATION OF BROWNING GENES BY SIRT1 ACTIVATION IN 3T3-L1 CELLS - Hamzah, Siti Sarah; Seman, Norhashimah Abu; Zamri, Liyana Ahmad; Abdullah, Shazana Rifham (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Obesity is the cause of over 4 million deaths each year according to the Global Burden of Disease study. It is characterized by an increase in adipocyte number and size, making adipogenesis an important target in the prevention and management of obesity. A possible approach is to induce adipose cells into becoming thermogenesiscompetent, such as brown or beige adipose cells. In this study, the effect of activating Sirtuin1 (Sirt1) in 3T3-L1 and its role in promoting the browning of white adipose cells was investigated. METHODOLOGY White pre-adipocyte cell lines 3T3-L1 were treated with Sirt1 activator (SRT1720) 2.5 mM, Sirt1 inhibitor (EX527) 10 mM or rosiglitazone (positive control for adipogenesis) 50 mM throughout ten days of adipogenic differentiation period. The effect of these treatments was assessed by western blotting, oil red O lipid staining and real-time PCR. RESULTS Inducing Sirt1 activity affected intracellular lipid accumulation. This was based on the observation of lesser accumulation of lipid in Sirt1-activated cells stained with oil red O. In contrast, when Sirt1 activity was attenuated by Sirt1-specific inhibitor, lipid production increased. Further investigation showed that the expression of genes critical for brown adipose tissue regulation, such as PGC1a and Cidea, were found to be elevated when Sirt1 activity was induced. CONCLUSION This work shows that targeting Sirt1 activity in white adipose cells would instigate an underlying molecular network that modulates the adipogenesis process during cell differentiation by producing less lipid. It also promotes the cells to differentiate into brown-like adipose cells that have better thermogenic capability. This can serve as a target for further investigation for therapeutic intervention in obesity.